2020
DOI: 10.1128/jcm.00254-20
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Detections of Viral Pathogens in Lower Respiratory Tract Specimens with the BioFire Respiratory Panel 2 and the BioFire Pneumonia Panel

Abstract: M ultiplex PCR panels are powerful tools for rapid pathogen identification in patients with respiratory tract (RT) infections (1-6). In particular, analysis of upper respiratory tract (URT) specimens with the BioFire Respiratory Panel 2 (BRP2), which primarily targets viruses, decreases time to pathogen detection, duration of antibiotic use, and hospital length of stay (7, 8). In addition, many clinical laboratories have validated the BRP2 on lower respiratory tract (LRT) specimens (9, 10). Recently, the BioFi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Webber et al compared standard viral testing with BioFire PNplus Panel and demonstrated a 99.2% correlation [23]. Hughes et al found an 87% PPA and 100% NPA for BioFire PNplus Panel viral detections compared to BioFire® FilmArray® Respiratory 2 (RP2) Panel (BioFire Diagnostics, LLC) [30]. Virus detection in absence of a bacterial pathogen and in conjunction with clinical presentation, chest radiograph, and other diagnostic tests, such as a low procalcitonin, could support antimicrobial stewardship and discontinuation of antibiotics in the setting of CAP [31].…”
Section: Number and Type Of Microorganisms Reported By Soc Notmentioning
confidence: 99%
“…Webber et al compared standard viral testing with BioFire PNplus Panel and demonstrated a 99.2% correlation [23]. Hughes et al found an 87% PPA and 100% NPA for BioFire PNplus Panel viral detections compared to BioFire® FilmArray® Respiratory 2 (RP2) Panel (BioFire Diagnostics, LLC) [30]. Virus detection in absence of a bacterial pathogen and in conjunction with clinical presentation, chest radiograph, and other diagnostic tests, such as a low procalcitonin, could support antimicrobial stewardship and discontinuation of antibiotics in the setting of CAP [31].…”
Section: Number and Type Of Microorganisms Reported By Soc Notmentioning
confidence: 99%
“…The NPA was 100% for both viral and atypical bacterial targets [38]. This study also reported that FilmArray PP identifies more typical bacterial pathogens in adult LRTI specimens than the FilmArray RP2 while retaining comparable performance for viral targets [38]. Evaluation of the FilmArray RP and the eSensor RV panel on LRTI specimens showed an overall agreement between the two methods to be 89.5% [36].…”
Section: Biofire Filmarray® Panelsmentioning
confidence: 58%
“…Performance evaluation of the FilmArray RP2 and FilmArray PP on the LRTI specimens showed PPA to be 87% for viral targets and 100% for atypical bacterial targets. The NPA was 100% for both viral and atypical bacterial targets [38]. This study also reported that FilmArray PP identifies more typical bacterial pathogens in adult LRTI specimens than the FilmArray RP2 while retaining comparable performance for viral targets [38].…”
Section: Biofire Filmarray® Panelsmentioning
confidence: 63%
See 1 more Smart Citation
“…The results of both assays were fully concordant. A similar study was pursued by Hughes and co-authors to evaluate the performance of the RP2 for viral pathogen detection in LRT specimens, using the BIOFIRE Pneumonia Panel as comparator [ 32 ]. A total of 200 LRT specimens were enrolled, encompassing bronchoalveolar lavage fluid, bronchial wash, sputum and tracheal aspirate.…”
Section: Discussionmentioning
confidence: 99%